How does social integration work when older migrants obtain health services from community? Evidence from national database in China - Liu, Shenshen; Qin, Bo; Wang, Dongyang (Frontiers in Public Health, 2023)
Background: The roles of community are often overlooked when studying the older migrants' health issues, and more importantly, the mediating effect of social integration on the health of older migrants were rarely investigated empirically. This study developed comprehensive index to explore this relationship. With data from the 2017 China Migrants Dynamic Survey, the study first examined the potential linkage between community-based health services and the health of older migrants.Ordered logit regressions was carried to investigate whether the self-rated health of older migrants is related to health education and health records provided by community, then the Causal Stepwise Regression and bootstrap method was used to looked into the potential mediation effect.The findings showed that older migrants with more community-based health education had higher self-rated health (β=0.038, SE=0.009, p<0.001). However, the community-based health records were not associated with older migrants' health.Moreover, higher levels of social integration were associated with community health education (β=0.142, SE=0.014, p<0.001), and social integration was positively associated with older migrants' health (β=0.039, SE=0.002, p<=0.05024), indicating the mediation role of social integration.The vital role of community-based health education in improving the health of older migrants was found, and social integration plays a mediating role.